Conhecimento e Sensitividade - Marques Segundo, L. H. (2020)
The subject matter of this dissertation is the nature of empirical knowledge. My view is that knowledge is at least sensitive true belief: one that the subject wouldn?t form or hold were it was false, but he would form it or hold it were it was true. I will argue that sensitivity is better understood functionalism, a true belief is knowledge only if (i) it is formed by a cognitive mechanism functioning properly (ii) in a proper environment, and this mechanism (iii) has to aim truth, (iv) having the tendency to produce more true beliefs than false ones, and (v) no defeater being available. I think that conditions (i) and (ii) can?t be adequately stated unless we take into account the sensitivity condition. The same is true for sensitivity: its better formulation is stated when we consider (i) and (ii). Roughly, I will argue that the sensitivity of one?s belief is a matter of its responsiveness to truth due to the proper function of one?s cognitive mechanism in a favorable environment: an environment where the subject wouldn?t form or hold the belief were it was false, but he would believe it were it was true. I begin, in Chapter I, with the following desideratum: to provide an anti-luck condition to knowledge. I argue that sensitivity is the main candidate to such condition. In Chapter II the standard version of sensitivity and some of the main difficulties to it are presented. Then, in Chapter III, I propose to understand sensitivity as inherent to proper functionalism and reply to the difficulties previously presented. A rival of sensitivity, the safety condition, is discussed in Chapter IV. I defend sensitivity over safety. Finally, in Chapter V, another important desideratum to any theory of knowledge is taken in consideration: skepticism. The adoption of sensitivity provides an attractive way to respond to skeptical argument, but at the coast of the rejection of closure principle, a very plausible epistemic principle. I will argue that we can adopt a restrict version of closure and that this restriction is predicted by sensitivity.